IMPROVING STUDENTS’ SPEAKING SKILL THROUGH SOMATIC, AUDITORY, VISUAL AND INTELLECTUAL (SAVI) TECHNIQUE AT THE SECOND GRADE STUDENTS OF SMP SWASTA PAB 2 HELVETIA MEDAN - Dea Kumala Sari; Dwi Suci Amaniarsih (Universitas Potensi Utama, 2021)
This research aimed to find out speaking skill of the second year students’ of SMP PAB 2 Helvetia Medan. The problem statement was: “To what extent can the use of SAVI (Somatic, Auditory, Visual, and Intellectual) Technique Improve the Students’ Speaking of the second Grade of SMP PAB 2 Helvetia Medan? The objective of the research was to find out Effectiveness of Using SAVI Technique to improve the Students’ Speaking skill. The researcher applied Class Action Reseacrh (CAR) method. The population of the research was of second Grade SMP PAB 2 Helvetia Medan which consisted of 36 students’. Researcher obtained data qualitative and quantitative data, the result showed the improvement students’ speaking ability through SAVI there were 80,19% who passed the Minimum Mastery Criteria (KKM) >60. This resulted come from data in the first cycle I and cycle II. In the cycle I in pre-test I, there were 7 students who succeeded with percentage of 19% and 13 students who did not succeed with a percentage 36% , and the cycle I, there were 5 students who succeeded with percentage 14% and 5 students did not succeeded with a percentage 14% then in the cycle II, there were 19 students who succeeded with percentage 53% and 4 students did not succeeded with a percentage 11% in post-test II. After treatment, their speaking aspect significantly improved. It can be said that SAVI (Somatic, Auditory, Visual, and Intellectual ) is effective to improve the students’ speaking.